Tailoring success: How individualised learning and increased awareness can combat dropout in skill development programs - Kala V. Krishnan; Murale Venugopalan; Padma Rao Sahib (Journal of Open Innovation: Technology, Market and Complexity)
The study aims to identify the factors associated with dropping out from government-supported skill certification programs, as perceived by the dropouts, their trainers, and their family members. This research contributes to the general topic of analysing the antecedents of dropouts from educational programs. To pursue our objective, a qualitative study involving a total of 17 in-depth interviews with trainees who discontinued participation in the skill certification program, their family members, and trainers was conducted. The study related educational dropout to a number of factors at the micro, meso, macro, and exosystem levels. Though there was general agreement among the trainees, trainers, and their family members regarding issues related to attendance and scheduling and government policy, opinions varied regarding the influence of other factors. The study discovered that by addressing the lack of awareness and providing courses that are more customized to individual needs and abilities, skill certification programs can reduce dropout. This research contributes to open social innovation by integrating diverse perspectives to develop actionable solutions for skill certification programs and promotes community-centered, accessible educational frameworks for sustainable social impact.